Impact of Fiscal Policies on the Economic Growth of Kosovo, Albania and North Macedonia - Cenaj, Aulonë; Bexheti, Abdylmenaf (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
The main objective of this research is to analyze the impact of fiscal policy on economic growth, for the Republic of Kosovo, Albania and North Macedonia and the period 2000-2023. The data used in this research are secondary data and are generated from official data published by the World Bank and the International Monetary Fund. The results of this study were analyzed through the Stata program, and data testing was carried out through standard multiple regression analysis, Hausman Taylor test, GEE model, GMM model, fixed effect and random effect. Based on the results, we may conclude that the increase in income, gross debt, and government expenditures positively affect the GDP of Kosovo, Albania and North Macedonia, whereas inflation negatively affects economic growth. There is a positive relationship between income, gross debt, government spending and GDP. This research aims to analyze the impact of fiscal policy on the economic growth of the Republic of Kosovo, Albania and North Macedonia for the period 2000-2023. As such, this research can be used as a basis for future work in this area.